Utilization of Digital Platforms in Realizing SDG 8.3 Entrepreneurship in MSMEs with the 9F Model Approach: A Study on the Hijab Fashion Business in Sidoarjo District, East Java. - Khairinia Kusuma, Alvitariani; Ratna Lindawati Lubis (Publisher Cv. Inara, 2024)
The utilization of digital platforms has become a key strategy to increase the competitiveness of MSMEs in Indonesia, particularly in the hijab fashion sector. This study aims to analyze the impact of digital platforms and the implementation of the 9F Entrepreneurship Model on MSMEs in Sidoarjo District, as well as its contribution to achieving Sustainable Development Goal (SDG) 8.3, which focuses on promoting economic productivity and entrepreneurship. This qualitative research employs a case study method involving five MSMEs in the hijab fashion industry, selected through purposive sampling. Data were collected through in-depth interviews and direct observations of business owners. The findings indicate that integrating digital platforms such as Instagram, WhatsApp, Facebook, Shopee, and TikTok with the 9F model significantly enhances innovation, visibility, and flexibility in MSMEs’ responses to market changes. Among the 169 MSMEs in the fashion sector in Sidoarjo, 26 focus on hijab fashion, with five MSMEs participating in this research. These MSMEs reported improvements in market reach and operational efficiency through digital platforms. Additionally, the integration of digital strategies supports economic growth aligned with SDG 8.3. This approach shows that the combination of digital platforms and the 9F Entrepreneurship Model can be an essential strategy for developing MSMEs in the hijab fashion sector, contributing to local economic growth and government efforts to achieve SDG 8.3. Keywords: MSMEs, digital platforms, 9F entrepreneurship, SDG 8.3, hijab fashion